Does the environmental Kuznets curve for deforestation exist for Ghana? Evidence from the bootstrap rolling window Granger causality test approach - Michael Kaku Minlah; Xibao Zhang; Philipine Nelly Ganyoh; Ayesha Bibi (Forestry Economics Review, 2021)
Purpose – This study investigates the existence of the environmental Kuznets curve (EKC) for deforestation for Ghana over the 1962–2018 the time period. Design/methodology/approach – The study employs a time-varying approach, the bootstrap rolling window Granger causality test to achieve its set objectives. Findings – The results from our study reveals an inverted “N” shape EKC for deforestation, implying that deforestation will initially decrease with increases in economic growth up to a certain income threshold and increases with further increases in economic growth beyond this income threshold up to a higher income threshold and then decrease with further increases in economic beyond the higher income threshold. Practical implications – The results from the study project show that over time economic growth can serve as a natural panacea to cure and mitigate the ills of deforestation that have plagued Ghana's forests over the years. Social implications – The results further highlight the important role of strong institutions in fighting the deforestation menace. Originality/value – The originality of this study lies in its methodology which allows for feedback from deforestation to the economy. This is in contrast to earlier studies on the EKC for deforestation which allowed causality only from deforestation to the economy.